Immunoglobulin synthesis by human peripheral lymphocytes and thymocytes in vitro. Specificity of immunochemical methods and stimulation by phytohaemagglutinin - Forbes, I. J. (1969)
Antibody–antigen precipitates were formed in solutions of radioactive products of human lymphocytes. The amount of radioactive material co-precipitating with non-specific, apparently unrelated, antibody–antigen precipitates was of the same magnitude as that co-precipitating with related, specific precipitates of IgG–anti-IgG or Tg–anti-Tg. Treatment of the solutions with an unrelated EA–anti-EA precipitate readily removed material capable of reacting with IgG–anti-IgG or Tg–anti-Tg precipitates. By contrast the evidence obtained with the technique of autoradiography of immunoelectrophoresis patterns indicated that the labelling of immunoglobulin arcs, and of a specific antibody–antigen precipitate, was specific. Only products of the lymphocyte from a subject with Hashimoto's disease labelled a Tg–anti-Tg line, although the control preparations from normal lymphocytes labelled the immunoglobulin arcs on the other side of the pattern. When mouse serum was used as carrier, and the immunoelectrophoresis was developed with rabbit anti-mouse serum, the immunoglobulin lines were not labelled. Products of human lymphocytes did not label an EA–anti-EA line in the immunoelectrophoresis. The anodal ends of gels were eluted after electrophoresis of radioactive products synthesized by lymphocytes. The amount of material co-precipitating in these eluates with specific precipitates was 1·8 times greater than that adhering to non-specific precipitates. These data raise the possibility that immunoglobulin molecules may be non-specifically adsorbed to unrelated antigen–antibody precipitates. The data indicated that phytohaemagglutinin stimulated synthesis of immunoglobulin was less than the overall increase of protein synthesis. Phytohaemagglutinin sometimes stimulated the total protein synthesis while inhibiting IgG synthesis.